Dependence or constraints? Labor supply responses from a cash transfer program - Diego Alejandro Vera Cossio (Inter-American Development Bank (IDB), 2019)
Decreases in labor supply among cash-transfer recipients are often cited as potential drawbacks of social-assistance programs. However, cash transfers can also increase employment. Using variation across cohorts and over time in the eligibility criteria of a nationwide conditional cash-transfer program in Bolivian public schools, this paper shows that employment increases among parents of eligible children, particularly for females. The increase in employment coincides with increases in self-employment and in the probability of investing in family businesses. These effects are mostly driven by females from areas with limited access to financial services. As mothers work more, overworked fathers reduce work hours. The results suggest that there are (positive) unintended consequences of cash-transfer programs targeting households with school-age children: Cash transfers may relax liquidity constraints and boost entrepreneurship, and also relieve overworked adults.
Keywords: D13; J46; J21; J22; O12; O18; 330; Cash transfers; Labor Supply; Gender; Entrepreneurship